Energy Security: Can we Cope with a Crisis? - Daly, John Charles; Bradley, Bill.; American Enterprise Institute for Public Policy Research (Washington: American Enterprise Institute, 1981)
An AEI (American Enterprise Institute) published dialogue on energy security held November 10, 1980.
held on November 10, 1980 and sponsored by the American Enterprise Institute for Public Policy Research
ne 18/04/2018
Loans
Keywords: Energy Policy; National Security